Pengaruh Pembelajaran dengan Metode e-Learning Terhadap Pemahaman Materi Kuliah Keperawatan Medikal Bedah II pada Mahasiswa Keperawatan Semester IV STIKes Maranatha Kupang - Ni Made Merlin; Antonius Rino Vanchapo (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Introduction: The development of technology has an impact on the realm of education, particularly in the form of an electronic-based learning method (e-learning). The application of the e-learning method for studying is considered as a way to enhance knowledge, specifically for nursing science to be more efficient during the COVID-19 pandemic. Purpose: This study aims to examine the effect of the e-learning method on the understanding of second-year nursing students toward surgical-medical nursing lecture material in STIKes Maranatha Kupang. Methods: The research design used in this study was a quasi-experimental design with one group pre-post test only. Respondents in this study were 39 people. Data collection was conducted by measuring students' comprehension of the topic of the course being taught. The study material was given through the online system for 150 minutes using the zoom application. Subsequently, respondents were remeasured with the same questions after the lecture session using the edLink application. The statistical test in this study used the Wilcoxon test. Results: The preliminary test obtained a mean of 32.69 with min-max 0-60 and post-test 71.79 with min-max of 55-90. The statistical test result of the p-value was 0,002. Conclusion: The increase of mean value after the post-test and also the statistical test results of p-value < 0.005 provide the evidence that the e-learning method affects the second-year nursing students’ comprehension concerning the material of medical-nursing courses in STIKes Maranatha Kupang. Keywords: e-learning method; understanding; medical-surgical nursing; course material